2011
DOI: 10.2114/jpa2.30.15
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Psychosocial Stress, Age, BMI, CRP, Lifestyle, and the Metabolic Syndrome in Apparently Healthy Subjects

Abstract: The aim of this cross-sectional study was to examine the factors which may be associated with the metabolic syndrome by exploring the relationship between psychosocial stress, age, body mass index (BMI), C-reactive protein (CRP), lifestyle factors, and the components of the metabolic syndrome, such as glycated hemoglobin (HbA1c), fasting blood sugar (FBS), body fat percentage, and triglyceride concentration, among apparently healthy subjects. Psychosocial stress was measured by the use of the inventory to meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
41
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 58 publications
7
41
0
2
Order By: Relevance
“…In this study, women with higher stress had less health-promoting behavior, and these findings were consistent with the findings of Starket et al, the relationship between perceived stress and health-promoting behaviors in high risk pregnant women. 18 These findings are also consistent with the results of other several studies. 29,30 In this study, women who showed less stress had better nutrition.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, women with higher stress had less health-promoting behavior, and these findings were consistent with the findings of Starket et al, the relationship between perceived stress and health-promoting behaviors in high risk pregnant women. 18 These findings are also consistent with the results of other several studies. 29,30 In this study, women who showed less stress had better nutrition.…”
Section: Discussionsupporting
confidence: 92%
“…Health promoting behaviors has attracted wide attention in the research as a key factor in health improvement. 18 But there is limited research evidence in this area for pregnant women with disease. The reason is the anticipated result that women with complications may be less likely to develop health promoting behaviors, and experience more stress than women with normal pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…34, Nº 2, mayo-agosto The hypertensive heavy smoker here described was also a passive smoker at home. Epidemiological and experimental studies have disclosed relationships between smoking, hypertension and dyslipidemia, both in diabetic and in non-diabetic individuals 8,9 . Smoking is associated with dyslipidemia, increased glicated haemoglobin, and metabolic syndrome 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological and experimental studies have disclosed relationships between smoking, hypertension and dyslipidemia, both in diabetic and in non-diabetic individuals 8,9 . Smoking is associated with dyslipidemia, increased glicated haemoglobin, and metabolic syndrome 9 . Nicotine can increase proteinuria, glomerular hypertrophy, and mesangial area in diabetic mice, in association with increased NADPH oxidase 4 , nitrotyrosine, and Akt expression 8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation